Educação de jovens e adultos/EJA: diálogos do estágio de docência na EJA, com o projeto pedagógico do curso/PPC de pedagogia e as implicações na formação docente - SANTANA, Maria Eduarda Pereira (2019)
In this work we approach the Education of Young and Adults. The research has as a research problem: what is the place of Youth and Adult Education, in the dialogue with the Pedagogical Project of the Pedagogy Course? The study of qualitative approach had as instruments of data collection: the report of the teaching experience in the EJA, two interviews with subjects of the EJA; and the Pedagogical Project of the Pedagogy Course. The authors who favored the dialogue on EJA were: Freire (1996) Gadotti (2011), Haddad (2009) on Supervised Internship : Pimenta and Lima (2009). The results indicate the existence of the place of the EJA in the course of pedagogy, a place that favors the affirmation; the visibility of the theory-practice relationship, in the scope of the Teaching Internship in the EJA and in the dialogue as the PPC of the Pedagogy Course. In the study, the theoretical / practical approach was demonstrated that allows for several implications of the Teaching Internship in EJA, in the teacher training of the student, in the dialogue with the PPC, such as: the comprehension of the complexity in the practice of teaching practice in the EJA; the presence of singularity and diversity in the EJA; the role of the need for pedagogical practices committed to a humanizing conception in the EJA, with affectivity; these data were evidenced, between teacher and students in the classroom, in the internship school. Also, it was possible to characterize the limitations of the place of the EJA in the PPC such as: the question of the workload of the Internship in EJA, that could be extended; the absence of a specific discipline on EJA, able to substantiate the Stage in the PPC; the difficulty of traineeships in EJA classes, by the number of reduced classes, to include all undergraduates in formation at UFPA and other institutions and the offer data to be made only at night time.